Characterization of whey protein-based films incorporated with natamycin and nanoemulsion of α-tocopherol. Issue 4 (April 2020) - Agudelo-Cuartas, Camilo; Granda-Restrepo, Diana; Sobral, Paulo J.A.; Hernandez, Hugo; Castro, Wilson
Abstract: Food packaging materials are commonly derived from petroleum that increases global contamination; this raises the interest to evaluate raw material from renewable sources such as whey protein for the development of packaging materials, especially to produce active films. This research aimed to evaluate whey protein-based film properties when natamycin, nanoemulsioned α-tocopherol, or both were added. An oil-in-water (O/W) nanoemulsion of antioxidant (α-tocopherol) was prepared by microfluidization technique. Four films were prepared with different levels of natamycin and nanoemulsified α-tocopherol and were characterized in terms of physicochemical, mechanical, optical-properties, water vapor barrier, FTIR, microstructure, antioxidant and antimicrobial activity. The natamycin, nanoemulsified α-tocopherol, or both did not modify the moisture content of the films. Moreover lead to a significant reduction of tensile strength and elastic modulus, while presenting growth in the elongation at break. Film opacity, the total color difference, the UV-Vis light barrier, and the water vapor permeability values increased when compounds were incorporated into the film. The microstructure studies showed uniformly distributed porosity throughout the films. The addition of nanoemulsioned α-tocopherol into whey protein-based films provoked antioxidant activity and the addition of natamycin produced films with effectivity against C. albicans, P. chrysogenum, and S. cerevisiae, allowing develop a material appropriate for use as active food packaging. Abstract : Food Science, Food Technology, Materials Science, Nanotechnology, Nanoemulsion, Whey protein-based films, Active Packaging, α-tocopherol, Natamycin.